Sources of Volatility during Four Oil Price Crashes - Baffes, John (Taylor and Francis, 2015)
Previous sharp oil price declines have been accompanied by elevated ex-post volatility. In contrast, volatility was much less elevated during the oil price crash in 2014/15. We provide evidence that oil prices declined in a relatively measured manner during 2014/15, with a dispersion of price changes that was considerably smaller than comparable oil price declines. This finding is robust to using both descriptive and GARCH measures of volatility. Further, the US dollar appreciation exerted a strong influence on volatility during the recent crash; in contrast, the impact of equity market shocks was muted.